1973
DOI: 10.1677/joe.0.0570331
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oestradiol, Luteinizing Hormone and Progesterone During the Oestrous Cycle in the Beagle Bitch

Abstract: Recent reports have recorded changes in the concentrations of oestradiol-17\g=b\, progesterone and luteinizing hormone (LH) in the plasma of the Beagle bitch during the oestrous cycle and pregnancy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

1975
1975
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 3 publications
2
11
1
Order By: Relevance
“…The demonstration of a distinct oestradiol peak close to the onset of oestrus in the present study supports the hypothesis of Jones et al (1973a) that the increase in oestrogens stimulates the release of LH. Plasma oestrogens must have decreased to rather low levels in some bitches (Text-figs 1 and 2) at the time when ovulation probably occurred, and accords with findings for other species (Short, 1972).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The demonstration of a distinct oestradiol peak close to the onset of oestrus in the present study supports the hypothesis of Jones et al (1973a) that the increase in oestrogens stimulates the release of LH. Plasma oestrogens must have decreased to rather low levels in some bitches (Text-figs 1 and 2) at the time when ovulation probably occurred, and accords with findings for other species (Short, 1972).…”
Section: Discussionsupporting
confidence: 91%
“…Phemister et al (1973) and Holst & Phemister (1971) found that ovulation in bitches takes place from 1-2 days after the onset of oestrus, coinciding with the occurrence of the LH peak (Jones et al, 1973a). The demonstration of a distinct oestradiol peak close to the onset of oestrus in the present study supports the hypothesis of Jones et al (1973a) that the increase in oestrogens stimulates the release of LH.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The oestrous cycle in the dog is characterized principally by increasing peripheral blood oestrogen levels during pro-oestrus, followed by a surge in LH concentrations in late pro-oestrus when serum progesterone concentrations start to increase to reach maximum levels in early metoestrus (Concannon et al, 1975 ;Nett étal., 1975 ;Hadley, 1975a;Jones et al, 1973b;Masken, 1972); the increased oestro¬ gen and LH concentrations decline within 1-4 days of ovulation to basal levels for the rest of the cycle. During pregnancy the progesterone concentrations remain maximal up to about Day 35 before waning steadily to give basal levels by the time of parturition or during the early stages of lactation (Austad, Lunde &Sjaastad, 1976;Concannon et al, 1975;Hadley, 1975 b;Smith & McDonald, 1974;Jones, Boyns, Bell, Christie & Parkes, 1973c;Masken, 1972;Christie, Bell, Horth & Palmer, 1971 ;Bell, Christie & YoungLai, 1971).…”
Section: Pregnancymentioning
confidence: 99%
“…Moreover, as shown in figure 4, some of the cat follicles used in the incubations were probably in an advanced stage of maturation. It is possible that the follicles are active for a very short period of time prior to the onset of estrus as in the beagle bitch (Jones et al, 1973). On the other hand, HCG may be more similar to cat LH than to ovine LH since the testosterone response to HCG tended to be greater (table I, fig.…”
Section: Discussionmentioning
confidence: 99%